The Role of the Digital Economy in the Development of the Halal Industry and the Sharia Economy in Indonesia: SWOT Analysis - Azwar, Azwar; Saputra, Jumadil (JURNAL INDO-ISLAMIKA, 2023)
This study aims to analyze the strengths, weaknesses, opportunities, and threats as well as strategies for the role of the digital economy in the halal industry and Sharia economy development in Indonesia. This research is a qualitative descriptive study using literature study and SWOT analysis. The results of the study show that the ultimate strength of Indonesia's digital economy lies in the high growth in the number of Muslims and the growth in digital transactions. However, Indonesia's digital economy is still constrained by the lack of digital economy ability to respond to demand and the market as the main weakness. Meanwhile, the main opportunity lies in good government support. The threat that must be faced is the absence of regulations related to consumer protection in the digital sector. Among the strategic program that can be carried out is increasing digital sharia economic literacy and investment in Indonesia.